Hubungan Status Gizi, Persen Lemak Tubuh, RLPP, dan Asupan Natrium dengan Hipertensi pada Wanita Lansia - Adistira, Ross Mellyana; Komala, Ramadhana; Abdullah, -; Muharramah, Alifiyanti (Jurnal Gizi, 2022)
With age, the ability of body tissues decreases gradually in maintaining normal functions. Hypertension or the “silent killer” is state of blood pressure ≥140/≥90 mmHg. The worst consequence is death. The purpose is to know correlation of nutritional status, body fat percentage, waist-to-hip ratio (WHR), and sodium intake with hypertension in elderly women at Posyandu Lansia Gading Rejo, Lampung. Design of research was cross sectional with Simple Random Sampling technique. The research subjects were 76 people. Height was measured using a microtoice, body weight and body fat percentage using Bioelectrical Impedance Analyze (BIA), WHR using met-line, sodium intake using the Semi Quantitative-Food Frequencies Questionnaire. The data that has been obtained then tested for normality of the data with the Kolmogorov-Smirnov test and continued with the Spearman Rank Correlation Coefficient test. Based on the Spearman Rank Correlation test, there was a significant relationship between; nutritional status with hypertension (p=0,000 r=0,425), body fat percentage with hypertension (p=0,001 r=0,376), WHR with hypertension (p=0,012 r=0,268), and sodium intake with hypertension (p=0,000 r=0,496). The conclusion is nutritional status, percent body fat, waist-tohip ratio, and sodium intake have a significant relationship with hypertension in elderly women.Keywords: body fat percentage, elderly of woman, hypertension, nutritional status, sodium intake, waist-to-hip ratio